Revisiting Lithium‐ and Sodium‐Ion Storage in Hard Carbon Anodes. Issue 12 (12th February 2023) - Kim, Hoseong; Hyun, Jong Chan; Kim, Do‐Hoon; Kwak, Jin Hwan; Lee, Jin Bae; Moon, Joon Ha; Choi, Jaewon; Lim, Hee‐Dae; Yang, Seung Jae; Jin, Hyeong Min; Ahn, Dong June; Kang, Kisuk; et al.
Abstract: The galvanostatic lithiation/sodiation voltage profiles of hard carbon anodes are simple, with a sloping drop followed by a plateau. However, a precise understanding of the corresponding redox sites and storage mechanisms is still elusive, which hinders further development in commercial applications. Here, a comprehensive comparison of the lithium‐ and sodium‐ion storage behaviors of hard carbon is conducted, yielding the following key findings: 1) the sloping voltage section is presented by the lithium‐ion intercalation in the graphitic lattices of hard carbons, whereas it mainly arises from the chemisorption of sodium ions on their inner surfaces constituting closed pores, even if the graphitic lattices are unoccupied; 2) the redox sites for the plateau capacities are the same as those for the closed pores regardless of the alkali ions; 3) the sodiation plateau capacities are mostly determined by the volume of the available closed pore, whereas the lithiation plateau capacities are primarily affected by the intercalation propensity; and 4) the intercalation preference and the plateau capacity have an inverse correlation. These findings from extensive characterizations and theoretical investigations provide a relatively clear elucidation of the electrochemical footprint of hard carbon anodes in relation to the redox mechanisms and storage sites for lithium and sodium ions, thereby providing a more rational design strategy for constructing better hard carbon anodes. Abstract : A comprehensive comparison of the lithium‐ and sodium‐ion storage behaviors of hard carbon is conducted, yielding the key findings: the sloping voltage section is presented by the lithium‐ion intercalation in the graphitic lattices of hard carbons, whereas it mainly arises from the chemisorption of sodium ions. The intercalation preference and the plateau capacity have an inverse correlation.